Grazer movements exacerbate grass declines during drought in an African savanna. (31st December 2018) - Staver, A. Carla; Wigley‐Coetsee, Corli; Botha, Judith
Abstract: Rainfall variability, including drought, consistently translates into variation in grass productivity in savanna ecosystems. These variations in grass availability can impact grazer populations, which can in turn shape grass responses to drought. However, despite clear evidence that grazers move freely in response to forage and water availability, drought ecologists have mostly failed to consider how these landscape‐scale processes influence vegetation responses to drought. Here, we ask how rainfall variability and drought, in interaction with population dynamics and movement of large grazers, shape grass layer responses in extant savanna landscapes in Kruger National Park in South Africa. We found that grass biomass was highly responsive to rainfall variability; notably, grass declines during drought were especially severe—even more severe than previously documented elsewhere. Grazing probably contributed, exacerbating drought effects in droughted regions and spatially extending them into non‐droughted refugia, where grass biomass also declined. Moreover, the existence of these refugia potentially prevented a grazer population crash. Synthesis. Our current focus on the physiological effects of drought is probably insufficient for understanding vegetation responses to drought. A renewed focus on landscape processes, including animal movement, will be critical to predicting savanna responses to increasingly frequent extreme events. Abstract : Our current focus on the physiological effects of drought is probably insufficient for understanding vegetation responses to drought. A renewed focus on landscape processes, including animal movement, will be critical to predicting savanna responses to increasingly frequent extreme events. Editor's Choice